Numerical investigation of fully confined RC column with carbon fiber reinforced polymer when expose to fire - Zakaria, Nur Aqilah; Ismail, Ruqayyah; Ahmad Zakwan, Fariz Aswan; Ahmad, Hazrina; Rosle, Muhamad Firdaus; Mohd Hashim, Mohd Hisbany; Muhammad Rashid, Raizal Saifulnaz (Elsevier, 2023)
Despite the fact that reinforced concrete is widely recognized as a fire-resistant construction material, high temperatures exposure for an extended period of time can change the physical and chemical properties of steel and concrete, resulting in serious damage to RC structures and, ultimately, the collapse of the entire structural system. This poses a serious threat to human life. As a solution to these problems, carbon fiber reinforced polymer (CFRP) has become increasingly popular in buildings and infrastructure over the past few decades. It has been shown to be an effective application with reinforcing steel of reinforced concrete (RC) members, as it can significantly increase their load carrying capacity and ductility. When exposed to fire, the behaviour of reinforced concrete columns with full confined carbon fiber reinforced polymer (CFRP) will be the primary focus of this investigation. The study will be carried out using numerical analysis, specifically the Finite Element Method (FEM). The ABAQUS CAE software will be used to create three models for the purposes of this investigation. The results of the finite element modelling agreed very well with those of the experimental results, and the results of the numerical simulation indicate that when the elements are exposed to fire, the values of stress and strain decrease.